Strategies for sustainable desert tourism development in Libya: Strategies for sustainable desert tourism development in Libya (jornal of the libyan geographical society, 2009)
The tourism sector is one of the most important economic sectors that directly influences the economies of many countries in our contemporary world, as its revenues have become one of the important sources of national income, and one of the sources of hard currency that support the balance of payments.This sector is a driving force behind the economic and social development programs of these countries, particularly developing ones. It also contributes to providing a wide range of diverse employment opportunities. International statistics in the tourism sector indicate a growing number of tourists, having jumped from approximately 25 million in 1950.It reached approximately 700 million tourists in 2002. It is projected to reach approximately 1.6 billion tourists by 2020, while international revenues increased from $2.1 billion in 1950 to approximately $500 billion in 2002.
Keywords: Tourism sector; Tourism revenues; International returns